Finite element modelling of the mechanical behavior of papaya fruit under compression - Aina, Ademola M.; Harith, Hazreen H.; Hashim, Norhashila; Mohamad Shukery, Mohamad Firdza (Elsevier, 2025)
Fruit is susceptible to mechanical damage during harvesting, transportation, and storage, depending on whether the stress exceeds their yield threshold. The finite element analysis (FEA) is often used to simulate stress distributions, but heterogeneous material properties in fruit increases the computational cost. Papaya, an irregular-shaped fruit with thin skin, thick flesh, and high moisture content, is prone to mechanical injury. Stress analysis can aid in post-harvest handling management. Modelling papaya as a homogeneous material could reduce the computational cost associated with FEA. Therefore, this study investigates: (1) a single material model that best simulates papaya's mechanical response under compressive loading using FEA, (2) the variation in papaya's mechanical response when simulated with two types of 3D models and, (3) the variation in papaya's mechanical response when loaded from two different directions. Three material models were simulated: (i) linear elastic, (ii) bilinear elastic-plastic with defined hardening parameters, and (iii) viscoelastic with distinctive relaxation times and relaxation modulus values. The viscoelastic model best simulated papaya's mechanical response under compression (RMSE = 0.0001 MPa, MRE = 12 %). Results indicated no substantial difference in the mechanical response of papaya when using 3D scanned or CAD models. Lastly, the stress distribution within the fruit tissues varied significantly (up to 69 % deviation) when compressed transversely and longitudinally. This highlights the necessity to consider loading direction in mechanical assessments of fruit like papaya.